ANALISIS PENGENDALIAN KUALITAS DENGAN METODE STATISTICAL QUALITY CONTROL (SQC) PADA PABRIK TEMPE PAK ENIK - Laura Greace Sinaga B; Anak Agung Istri Agung Sri Komaladewi; Ni Luh Putu Lilis Sinta Setiawati; Gusti Ngurah Priambadi; I Gusti Agung Kade Suriadi; Desak Ayu Sista Dewi (Jurnal Riset Multidisiplin Edukasi, 2025)
The high level of competition in the food industry, especially in the MSME sector, requires producers to maintain product quality in order to meet consumer expectations. Pak Enik Tempe Factory as one of the MSMEs in Badung Regency, Bali, experiences problems related to high levels of defective products which have an impact on decreasing quality and customer satisfaction. This study aims to analyze quality control using the Statistical Quality Control (SQC) approach. Data collection was carried out during the period 1 December 2024 - 31 January 2025 using observation and interview methods. The tools used in the SQC method include: check sheets, flowcharts, histograms, scatter diagrams, Pareto diagrams, control charts, and fishbone diagrams. The results of the study showed that the most common types of defects were non-dense textures and black spots caused by human factors, work methods, materials, and machines. Through the Pareto Diagram, it is known that these two types of defects contribute 75% of the total product defects. Control Chart analysis shows that most of the production processes are still within control limits even though there are deviations at several points. The use of Fishbone Diagrams helps identify the root cause of major defects. The output of this research is in the form of recommendations for improving the production system so that the quality of tempeh increases and the number of defective products can be minimized. This research is expected to provide a real contribution in the development of a quality control system in MSMEs based on tempeh production.